Stakeholder perspectives of test administration in a Bangladeshi university: A qualitative study - Snigdha Sarmili Ria; Sheikh Md. Muniruzzaman (Englisia: Journal of Language, Education, and Humanities, 2026)
Learner achievement benchmarks are typically operationalized through tests and assessments; however, students at newly established public universities in Bangladesh encounter a range of obstacles that hinder their academic progress. Despite receiving equivalent instruction under comparable teaching and learning conditions, learner performance varies markedly. Students, teachers, and administrators constitute the three primary stakeholder groups in any testing procedure, and their respective social and personal backgrounds, institutional contexts, and situational realities fundamentally shape assessment practices. This study investigates factors affecting test administration through semi-structured interviews with 35 participants: 26 students, 7 faculty members from the Department of English at a public university pseudonymously referred to as Padma Science and Technology University (PSTU), and two administrators—one from the department and one from the institution at large. Employing a qualitative design, the study examines both undergraduate and postgraduate programs through thematic analysis of interview data gathered from the three stakeholder groups. The results reveal substantial complexities permeating the testing process from the perspective of test takers, while also indicating that teachers and administrators encounter obstacles and appear to be operating under considerable strain. The findings provide analytic insights for anticipating testing and administrative challenges in analogous contexts, as well as for identifying areas requiring targeted intervention. The findings suggest that the prevailing situation demands heightened attention to the testing environment, reform of assessment policies, reinforcement of stakeholder roles and responsibilities, and systematic attention to other contributing factors shaping test administration as a holistic process. The research underscores the importance of context-sensitive inquiry, recognizing that each educational setting presents unique pedagogical demands.  In so doing, the study emphasizes the critical role of context-specific formulations in fostering more effective and equitable test administration within Bangladeshi higher education.